The Last House On The Street - Chamberlain, Diane, 1950- (New York : St. Martin's Press, 2022)
"From bestselling author Diane Chamberlain comes an irresistible new novel that perfectly interweaves history, mystery, and social justice. When Kayla Carter's husband dies in an accident while building their dream house, she knows she has to stay strong for their four-year-old daughter. But the trophy home in Shadow Ridge Estates, a new development in sleepy Round Hill, North Carolina, will always hold tragic memories. When she is confronted by an odd, older woman telling her not to move in, she almost agrees. It's clear this woman has some kind of connection to the area...and a connection to Kayla herself. Kayla's elderly new neighbor, Ellie Hockley, is more welcoming, but it's clear she, too, has secrets that stretch back almost fifty years. Is Ellie on a quest to right the wrongs of the past? And does the house at the end of the street hold the key? Told in dual time periods, The Last House on the Street is a novel of shocking prejudice and violence, forbidden love, the search for justice, and the tangled vines of two families"--.
Keywords: Novels